A new approach to the analysis of homogeneous transfer lines with unreliable buffers subject to time-dependent failure - Xia, Beixin; Wang, Chen; Gao, Ya; Peng, Yunfang; Liu, Lei (International journal of production research, 2020)
This paper presents a new analytical approach to the analysis of transfer lines with unreliable machines and unreliable buffers running in a steady state. The buffers are assumed to be subject to time-dependent failure, i.e. they can fail in any condition, even when not loaded. As the most common representative of this type of buffer, accumulating conveyors are widely adopted in actual transfer lines. In this paper, a continuous model is established for such transfer lines in which the part flow is approximated by a continuous flow. Then, an efficient decomposition method based on a generalised exponential distribution is proposed to analyse the model. A new set of decomposition equations that take into account the mechanism of time-dependent failure are derived and then solved by an advanced algorithm. Extensive numerical experiments are performed. The results show that the proposed method is valid and efficient.